PERLINDUNGAN HUKUM TERHADAP IZIN USAHA PERTAMBANGAN BATU BARA DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Siti Soleha; Arrisman (INTELIGENSIA MEDIA, 2024)
Coal mining in Indonesia is a strategic sector but also sensitive because it is closely related to the economy and the environment. To regulate this activity, the Indonesian government has issued Law Number 25 of 2007 concerning Capital Investment. This law provides the legal basis for coal mining business permits, which includes requirements, procedures and legal protection. The purpose of this article is to analyze the legal protection of coal mining business permits in Indonesia based on Law Number 25 of 2007. The research method used is literature study to collect and analyze relevant legal data. The results of the analysis show that Law Number 25 of 2007 provides a comprehensive legal framework for coal mining business permits, including application procedures, conditions that must be fulfilled by applicants, and obligations that must be complied with by permit holders. Apart from that, this law also regulates sanctions for violators. However, there are still challenges in implementing this law, such as consistent law enforcement and adequate environmental protection. Therefore, further efforts are needed to ensure that legal protection for coal mining business permits in Indonesia can be carried out effectively in accordance with the spirit of the law.